Assessing Online Student Performance via participation, and Examinations as Alternative Measures - Tasie, George O. (Advances in Social Sciences Research Journal, 2021)
Online homework is a relatively new instruction and evaluation technique. While it appears to be an effective tool, empirical studies of its efficacy suggests they have not been done. This paper analyzes correlations among systematic class participation scores, online homework scores and test results from two sections of Effective People Management and two sections of Advanced Human Resource Management taught at a Middle Eastern University – University of Kurdistan Hewler in fall semester 2017.Collection of data were made in four classes of two modules with the outcomes and implications suggesting students were expected to attempt to work on each homework problem three times and were allowed as many attempts as they wished within time limits set by the instructor. Homework problems were made available for extra credit immediately after a new chapter was introduced